Mitochondrial dysfunction in models of Progressive Supranuclear Palsy. (20th December 2022) - Troutwine, Benjamin R; Lysaker, Colton R; Strope, Taylor A.; Swerdlow, Russell H; Wilkins, Heather M
Abstract: Background: Progressive Supranuclear Palsy (PSP) is a rare neurodegenerative disease hallmarked by tau pathology in both neurons and astrocytes. Familial forms of PSP are caused by mutations affecting tau ( MAPT ) while risk factors for sporadic PSP are largely unknown. Mitochondrial function declines during aging and mitochondrial dysfunction is observed in PSP. Generation of reactive oxygen species and mitochondrial dysfunction are thought to directly contribute to the production of tau deposits. Here we interrogated mitochondrial function in astrocytes and neurons derived from induced pluripotent stem cell models of sporadic and familial PSP. Methods: Induced pluripotent stem cells were obtained from healthy controls, patients with sporadic PSP, and PSP patients carrying a MAPT A152T mutation. iPSCs were differentiated into neurons and astrocytes following StemCell Technologies protocols. Mitochondrial function was assessed using the Seahorse XFe96 analyzer. Fluorescent stains were used to determine mitochondrial mass, mitochondrial membrane potential, mitophagy levels, mitochondrial turnover, and mitochondrial calcium levels. Results: Neurons derived from sporadic PSP and A152T tau patients had decreased mitochondrial respiration, increased mitochondrial superoxide, and increased mitochondrial mass. Astrocytes derived from sporadic PSP patients had increased mitophagy, mitochondrial turnover, mitochondrial calcium, and mitochondrial superoxide. Complex I and Complex IV activity were increased in sporadic PSP derived astrocytes, but in A152T tau astrocytes we observed decreased Complex I activity. Conclusion: Neurons and astrocytes derived from PSP patients show changes in mitochondrial function. Alterations are cell type specific and differ between sporadic and familial PSP models. We are working to determine how this contributes to tau pathology.